Pengaruh Digital Marketing Terhadap Penjualan Roti UMKM Hafizh Roti di Kecamatan Mandai Kabupaten Maros - Hikmah Hikmah; Mohammad Anwar Sadat; Asriyani Asriyani (Jurnal Agribis, 2026)
The objective of this study is to analyze the influence of digital marketing on the sales improvement of Hafizh Roti UMKM in Mandai District, Maros Regency. In today’s digital era, the utilization of information technology has become one of the main strategies to expand market reach, increase brand awareness, and encourage consumer purchasing decisions. The analytical technique used is multiple linear regression to examine the effect of social media and digital promotion variables on purchasing decisions. The results indicate that digital marketing has a significant influence, both simultaneously and partially, on increasing Hafizh Roti sales. Social media and digital promotion have positive and significant coefficients in driving consumer purchasing decisions. Furthermore, it was found that 79% of respondents learned about Hafizh Roti through social media and were interested in purchasing due to the implemented digital promotions. This study emphasizes the importance of digital marketing strategies for UMKM in enhancing competitiveness in the modern era.